Carbon Dioxide Emissions as Affected by Alternative Long-Term Irrigation and Tillage Management Practices in the Lower Mississippi River Valley - S. F. Smith; K. R. Brye (The Scientific World Journal)
Ensuring the sustainability of cultivated soils is an ever-increasing priority for producers in the Lower Mississippi River Valley (LMRV). As groundwater sources become depleted and environmental regulations become more strict, producers will look to alternative management practices that will ensure the sustainability and cost-effectiveness of their production systems. This study was conducted to assess the long-term (>7 years) effects of irrigation (i.e., irrigated and dryland production) and tillage (conventional and no-tillage) on estimated carbon dioxide (CO2) emissions from soil respiration during two soybean (Glycine max L.) growing seasons from a wheat- (Triticum aestivum L.-) soybean, double-cropped production system in the LMRV region of eastern Arkansas. Soil surface CO2 fluxes were measured approximately every two weeks during two soybean growing seasons. Estimated season-long CO2 emissions were unaffected by irrigation in 2011 (P>0.05); however, during the unusually dry 2012 growing season, season-long CO2 emissions were 87.6% greater (P=0.044) under irrigated (21.9 Mg CO2 ha−1) than under dryland management (11.7 Mg CO2 ha−1). Contrary to what was expected, there was no interactive effect of irrigation and tillage on estimated season-long CO2 emissions. Understanding how long-term agricultural management practices affect soil respiration can help improve policies for soil and environmental sustainability.